Research on distributed data spatial architecture model for ownership governance - SUN Jinye; GUO Shuxing (大数据)
At present, the top-level system of ownership governance in China needs to be systematized and improved, and problems such as an imperfect transaction mechanism and a low level of data circulation and sharing are identified, which hinder the marketization process of data elements and inhibit the full release of their value. Based on the above background, firstly, the theoretical basis of ownership governance for cross-domain data flow was explored from four perspectives: value network theory, ecological synergy theory, architect theory, and financial trust theory. Subsequently, a distributed data space architecture model based on the perspective of cross-domain collaboration for data authorization operators was innovatively proposed by combining distributed architecture theory with dynamic It is found that the architecture model can effectively guide the application of cross-domain scenarios so that different dimensions' data can generate large-scale gain value through superposition and optimize ownership allocation to improve orderliness in data market transactions.